2013
DOI: 10.1074/jbc.m112.439455
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism by Which a Potent Hepatitis C Virus NS3-NS4A Protease Inhibitor Overcomes Emergence of Resistance

Abstract: Background: Antivirals must often be given in combinations to avoid rapid emergence of resistance. Results: We identified and structurally characterized protease inhibitors that maintain potency against genotype and resistant variants. Conclusion: Pan-variant potency was achieved by targeting invariant regions and incorporating flexibility where pocket variability occurs. Significance: Such inhibitors may yield simplified and/or more successful treatments for hepatitis C infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…45 For carbamate-linked P4 capping groups, generally bulky hydrophobic moieties are preferred but the size of the group appears to be dependent on the heterocyclic moiety present at the P2 position. 35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 For carbamate-linked P4 capping groups, generally bulky hydrophobic moieties are preferred but the size of the group appears to be dependent on the heterocyclic moiety present at the P2 position. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Disruption of electrostatic interactions between Arg155 and Asp168 due to mutations underlies drug resistance against NS3/4A PIs. 3133,35 Moreover, we have shown that structural differences at the P2 moiety largely determine the resistance profile of these inhibitors. 36 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by a recent report detailing a P 4 capping SAR in a faldaprevir derivative. 52 …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the P2 moiety constraint reducing the inhibitor's ability to adapt to changes resulting from HCV protease mutations. In addition, the recently published crystal structures of several inhibitors in complex with the major drug resistant mutants have revealed the molecular basis underlying the unique resistance profiles of these inhibitors, [34][35][36] and will provide useful information for further designing macrocyclic PIs against a wider spectrum of HCV PI-resistant mutants. Tremendous progress has been made in the discovery and development of macrocyclic HCV PIs over the past decade.…”
Section: Resultsmentioning
confidence: 99%